Auto tuning of frequency on wireless power transfer for an electric vehicle - Kazuya Yamaguchi; Kenichi Iida (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In these days, electric vehicles are enthusiastically researched as a countermeasure to air pollution, although these do not have practicality compared to gasoline-powered vehicles. The aim of this study is to transport energy wirelessly and efficiently to an electric vehicle. To accomplish this, we focused on frequency of an alternating current (AC) power supply, and suggested a method which determined the value of it constantly. In particular, a wireless power transfer circuit and a lithium-ion battery in an electric vehicle were expressed with an equivalent circuit, and efficiency of energy transfer was calculated. Furthermore, the optimal frequency which maximizes efficiency was found, and the behavior of voltage was demonstrated on a secondary circuit. Finally, we could obtain the larger electromotive force at the secondary inductor than an input voltage.